Heparin-induced thrombocytopenia associated with polycythemia vera during the treatment of acute coronary syndrome - Yoshizane, Takashi (J Cardiol Cases, 2016)
Here, we report a case of heparin-induced thrombocytopenia (HIT) associated with polycythemia vera (PV) during the treatment of acute coronary syndrome. An 84-year-old woman with pre-existing PV had an acute myocardial infarction and developed HIT after using heparin. An additional myocardial infarction was caused by HIT, and caused marked damage to her cardiac function. However, she was successfully treated with argatroban infusion and intensive care. In this case, we suspected HIT at an extremely early stage, when the decline in platelet count remained at 16%, which might have prevented further thrombosis. Subsequently, the nadir in the platelet count remained at 32%, which resulted in “intermediate possibility of HIT” according to the 4Ts score; thus, further detailed serological examination may be required for accurate diagnosis of HIT. <Learning objective: The main contribution of our paper is that it reveals that clinicians should exercise caution when treating patients with polycythemia vera (PV) because they are prone to serious thrombotic complications and the presence of PV may obscure the occurrence of heparin-induced thrombocytopenia because of atypical fluctuations in platelet counts. We believe that this contribution is theoretically and practically relevant because it includes findings that could enhance clinical treatment and outcomes among such patients.>